2014
DOI: 10.3390/photonics1040390
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Wave Propagation Through Saturable Nonlinear Oligomers

Abstract: In the present paper we consider nonlinear dimers and trimers (more generally, oligomers) embedded within a linear Schr{\"o}dinger lattice where the nonlinear sites are of saturable type. We examine the stationary states of such chains in the form of plane waves, and analytically compute their reflection and transmission coefficients through the nonlinear oligomer, as well as the corresponding rectification factors which clearly illustrate the asymmetry between left and right propagation in such systems. We ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 28 publications
(43 reference statements)
7
19
0
Order By: Relevance
“…Later, in the context of asymmetric transmission of signals through non-linear asymmetric dimer layers, it was shown that multistability could be enhanced by weak saturation of the (cubic) on-site nonlinearity; this favors the nonreciprocal transmission and also yields opposite effects of the rectifying action for short/long wavelength signals [7,8]. A similar study was carried out for saturable nonlinear oligomer DNLS segments (N = 1, 2, 3) embedded in a linear Schrödinger chain [9]. Other relevant works concern the asymmetric wave transmission through oligomers with cubic-quintic on-site nonlinearity [10], and the enhancement of the non-reciprocal transmission under saturable cubic-quintic nonlinear responses for dimers [11].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Later, in the context of asymmetric transmission of signals through non-linear asymmetric dimer layers, it was shown that multistability could be enhanced by weak saturation of the (cubic) on-site nonlinearity; this favors the nonreciprocal transmission and also yields opposite effects of the rectifying action for short/long wavelength signals [7,8]. A similar study was carried out for saturable nonlinear oligomer DNLS segments (N = 1, 2, 3) embedded in a linear Schrödinger chain [9]. Other relevant works concern the asymmetric wave transmission through oligomers with cubic-quintic on-site nonlinearity [10], and the enhancement of the non-reciprocal transmission under saturable cubic-quintic nonlinear responses for dimers [11].…”
Section: Introductionmentioning
confidence: 88%
“…The parameter γ n determines the strength of the local nonlinearity, which we take to have a standard cubic (Kerr) form, while n represents the nonlocal (inter-site) saturable nonlinearity. We saturate only the inter-site nonlinearity as the effect of saturating the on-site cubic nonlinearity has been addressed in earlier work [7][8][9]11]. β is the saturation parameter; in the unsaturated limit β = 0 we recover the DNLS model with cubic inter-site nonlinearity studied in [18] (relevant e.g.…”
Section: Modelmentioning
confidence: 99%
“…If D = i −1 δ and m = γ, eqs. (31), become the time dependent saturable nonlinear Schrödinger equation, [4]: 5 The equilibrium function in the d2q9 velocity scheme.…”
Section: The Construction Of the Nonlinear Schrödinger Equationmentioning
confidence: 99%
“…For example, for short and high peak power pulses, the field-induced change in the refractive index cannot be described by a Kerr-type nonlinearity, since it is influenced by higher-order nonlinearities such as saturable nonlinearity [24]. The saturation of the nonlinear response has been shown to have novel impacts on the dynamical properties of wave propagation in clean systems [24,25,26,27,28,29,30,31,32,33,34,35]. For instance, it has been pointed out that the saturable nonlinearity allows the existence of stable two-state solitons with the same time duration [24] and of breathers with high power [25].…”
Section: Introductionmentioning
confidence: 99%
“…In [26], genuinely localized travelling waves have been found in saturable nonlinear Schrödinger lattices for the first time. Furthermore, in recent papers, the authors have shown that there exists asymmetric wave propagation through saturable nonlinear oligomers and wave rectification devices can be produced based on such systems [34,35].…”
Section: Introductionmentioning
confidence: 99%